Isolation and Characterization of Multidrug-Resistant Escherichia coli and Salmonella spp. from Healthy and Diseased Turkeys - Md. Tawyabur; Md. Saiful Islam; Md. Abdus Sobur; Md. Jannat Hossain; Md. Muket Mahmud; Sumon Paul; Muhammad Tofazzal Hossain; Hossam M. Ashour; Md. Tanvir Rahman (MDPI AG, 2020)
Diseases caused by Escherichia coli (E. coli) and Salmonella spp. can negatively impact turkey farming. The aim of this study was to isolate and characterize multidrug-resistant (MDR) E. coli and Salmonella spp. in healthy and diseased turkeys. A total of 30 fecal samples from healthy turkeys and 25 intestinal samples from diseased turkeys that died of enteritis were collected. Bacterial isolation and identification were based on biochemical properties and polymerase chain reaction (PCR). Antibiogram profiles were determined by disk diffusion. The tetracycline-resistance gene tetA was detected by PCR. All samples were positive for E. coli. Only 11 samples (11/30; 36.67%) were positive for Salmonella spp. from healthy turkeys, whereas 16 (16/25; 64%) samples were positive for Salmonella spp. from diseased turkeys. E. coli isolated from diseased turkeys showed higher resistance to levofloxacin, gentamicin, chloramphenicol, ciprofloxacin, streptomycin, and tetracycline. Salmonella spp. isolated from healthy turkeys exhibited higher resistance to gentamicin, chloramphenicol, ciprofloxacin, streptomycin, imipenem, and meropenem. All E. coli and Salmonella spp. from both healthy and diseased turkeys were resistant to erythromycin. Salmonella spp. from both healthy and diseased turkeys were resistant to tetracycline. Multidrug resistance was observed in both E. coli and Salmonella spp. from diseased turkeys. Finally, the tetA gene was detected in 93.1% of the E. coli isolates and in 92.59% of the Salmonella spp. isolates. To the best of our knowledge, this is the first study to isolate and characterize tetA-gene-containing MDR E. coli and Salmonella spp. from healthy and diseased turkeys in Bangladesh. Both microorganisms are of zoonotic significance and represent a significant public health challenge.